1989
DOI: 10.1016/0035-9203(89)90507-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating anodic antigen levels in serum before and after chemotherapy with praziquantel in schistosomiasis mansoni

Abstract: The kinetics of serum levels of circulating anodic antigen (CAA) of Schistosoma mansoni were studied in patients with intestinal schistosomiasis before and after treatment with praziquantel. Day to day fluctuation in faecal egg excretion was compared with fluctuation in antigen level in 20 patients by serum and stool examination on 3 consecutive days before treatment. Antigen levels - calculated either as absorbance value of undiluted serum or as titre - showed less fluctuation than the number of eggs per gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…The test usually becomes negative within 1 week of successful anti-schistosomal therapy. 15,16 CAA testing was performed at the NIMR laboratory in Mwanza using the upconverting phosphor (UCP) technology lateral flow assay as previously described. 17,18 We used the strategy recommended by the WHO/the Special Programme for Research and Training in Tropical Diseases to define a composite reference standard for schistosome infection as the presence of schistosome eggs visualized microscopically and/or a serum CAA value ≥ 30 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The test usually becomes negative within 1 week of successful anti-schistosomal therapy. 15,16 CAA testing was performed at the NIMR laboratory in Mwanza using the upconverting phosphor (UCP) technology lateral flow assay as previously described. 17,18 We used the strategy recommended by the WHO/the Special Programme for Research and Training in Tropical Diseases to define a composite reference standard for schistosome infection as the presence of schistosome eggs visualized microscopically and/or a serum CAA value ≥ 30 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 The excretion of the schistosome-circulating antigens in the urine of infected patients makes possible the use of noninvasive techniques for simple diagnosis of schistosomiasis. [19][20][21][22] In addition, low fluctuations of urinary elimination of the circulating antigens have been observed. 23,24 Attallah and others 5 examined the presence of a 74-kD circulating antigen in the urine of infected and uninfected cases using Fast Dot-ELISA based on MAb BRL4.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on populations living in endemic areas, the levels of these antigens were found to be related to the presence of an active infection; following successful treatment, CAA and CCA levels became negative within 3-6 weeks (De Jonge et al 1989;Van Lieshout et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen levels are related to intensity of infection, as expressed by parasite egg excretion. In studies with hospitalized patients CAA and CCA levels dropped to zero within 3-6 weeks after successful chemotherapy (De Jonge et al 1989;Van Lieshout et al 1991, 1993.…”
Section: Introductionmentioning
confidence: 99%